Choosing fruit - berry fillings for condensed сanned milk with sugar - Ryabokon, Natalia; Rindyuk, Dmitry (My University, 2014)
The rheological and organoleptic properties of condensed canned milk with sugar and fruit fillings were determined. The syrups’ and jams’ usage in the technology of condensed canned milk with sugar reduces the viscosity of finished products and increase the length of the structures destruction in products with fruit jam. We studied the impact of fruit-berry jam on the indicators of conditional dynamic threshold fluidity and fluidity ratio of condensed canned milk with sugar and the possibility of losing the product’s fluidity during storage. In the CCM recipes with sugar and fruit - berry fillings, the preference should be given to fruit-berry syrup.
Keywords: effective viscosity; ефективна в’язкість; fruit fillings; рослинні наповнювачі; jam; джем; rotational viscometer; ротаційний візкозиметр; syrup; сироп